PENGARUH BERMAIN HURUF PUNGGUNG BERANTAI TERHADAP KEMAMPUAN MEMBACA AWAL ANAK USIA 5-6 TAHUN DI TK ANNUR SARI KUANTAN SINGINGI - Wulan Sari; Wilson '; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on field observations of the initial reading ability of students they begin to develop, some children can not distinguish between some letters that are similar, children are still difficult to connect tehe sound of the two letters into words, some children are still facing difficulties in connecting images with simple words, as well as reading picture books that have a simple sentence, and there are some children who can not read his own full name. So that the learning should be given in the form of imaginative play. This study aims to determine the effect of playing back a chain letter on early reading skills of children ages 5-6 years in TK Annur Sari Kuantan Singingi. Samples used in this study were 22 children. The data collection techniques are observation. Data analysis techniques using t-test using SPSS 20. The research hypothesis is that there is a significant influence back chain letters game on early reading skills of children ages 5-6 years in TK Annur Sari Kuantan Singingi. It can be seen from the analysis of data obtained t= 8,182 bigger than t table= 2,021 with a 5% error level. So it means, Ho= rejected and Ha= eccepted. It means in this study are the effect of early reading skills of children before and after palying back a chain letter in TK Annur Sari Kuantan Singingi. Testing the effect of playing back a chain letter to the child’s early reading skills using n-gain formula indicates the magnitude of the effect is 52%, which is medium category.